Classroom Management Styles, Teachers’ Job Performance and Students Academic Performance in Public Secondary Schools in Abuja, Nigeria (American Journal of Public Diplomacy and International Studies (2993-2157), 2025)
This study assessed the impact of classroom management styles on teachers’ job performance and students’ academic performance in Public secondary schools in Abuja, Nigeria. In this study, we used correlational survey method. The population comprises all the teachers and students in the Federal Capital Territory, Abuja, Nigeria. We used a sample size of 160 principals and 240 senior secondary schools students using Taro Yamen’s formula. Proportionate stratified random sampling was used to select the number of principals per area councils, while disproportionate stratified random sampling was used to select the number of students per areas councils for fair representation. The overall internal consistency reliability co-efficient indices obtained through Cronbach Alpha method were: 0.73 for (TMSQ), and 0.71 for (SCMSQ). Means, standard deviations, and Pearson Product Moment Correlation Co-efficient were used to answer the research questions, while regressions and associated t-tests were used to test the hypothesis at 0.05 level of significance. The study concluded that there was significant relationship between classroom management styles and teachers’ job performance in Public secondary schools in Abuja. The study also showed that there was significant relationship between Classroom Management styles and Students Academic Performance in Public Secondary school in Abuja. Based on the findings, the paper hereby recommends that Federal Capital Territory Board of secondary schools should organize training for teachers on effective use of classroom management styles. Federal Capital Territory Board of secondary schools should also organize training for teachers on how to manage the students in the classrooms in the schools for maximum academic performance.